Information and communication technology and the spatial evolution of mature cities. (June 2017) - Czamanski, Daniel; Broitman, Dani
Abstract: The great urbanization project that started some 10, 000 years ago is approaching its final stages. We focus on the spatial evolution of mature cities and on the possibility that information and communication technology will contribute to a phase transition and a start of a new urban life cycle. In a context of agent-based model that includes heterogeneous land developers, housing consumers and planning agencies, we speculate about conditions that may change cities as we know them. In particular, we propose a scenario in which the prevalent central city oriented metropolitan areas will be replaced by a multitude of sprawling cities. Highlights: We focus on the spatial evolution of mature cities. Information and communication technology will contribute to a start of a new urban life cycle. An agent-based model is used to test conditions that may change cities. ICT may contribute to replace metropolitan areas by multitude of medium size sprawling cities.